Lambda Association Board of Directors - Sahl, Ted (photographer):::Creator::::::::::::
Group photograph of the Lambda Association Board of Directors. Front row, left-to-right: Sal Accardi, Johnie Staggs, Myra Beals, and Dan Relic. Back row, left-to-right: Steve Century, Kent Olson, and Pat McAtee.